An Identification of Impacts of Area Expansion Policy of Oil Palm in Southern Thailand: A Case Study in Phatthalung and Nakhon Si Thammarat Provinces - Rattana, Unjan (ScienceDirect, 2016)
Demand for palm oil is stimulating a rapid expansion of area used for oil palm plantations in Thailand. This research aims at identifying both positive and negative impacts of area expansion policy of oil palm in southern Thailand using a case study in Phatthalung and Nakhon Si Thammarat provinces. Primary data were collected using semi-structured questionnaires. Local key informants were identified using purposive and snowball selection. The analytical tool was the Analytic Hierarchy Process AHP containing goal, criteria and specified impacts of area expansion policy of oil palm. The results revealed that economic impacts such as increase diverse investment opportunities, generating stable income and relative competition with other area are the most important positive impacts, while social impacts such as conflicts between the government and local people and prejudice in solving by the government are the most important negative impacts. The outcome can be utilized by policy makers and concerned parties to formulate appropriate policy options.